Universal aptamer-based real-time monitoring of enzymatic RNA synthesis - Höfer, Katharina; Langejürgen, Lisa V.; Jäschke, Andres (Journal of the American Chemical Society, 2013)
In vitro transcription is an essential laboratory technique for enzymatic RNA synthesis. Unfortunately, no methods exist for analyzing quality and quantity of the synthesized RNA while the transcription proceeds. Here we describe a simple, robust, and universal system for monitoring and quantifying the synthesis of any RNA in real time without interference from abortive transcription byproducts. The distinguishing feature is a universal fluorescence module (UFM), consisting of the eGFP-like Spinach aptamer and a highly active hammerhead ribozyme, which is appended to the RNA of interest (ROI). In the transcription mixture, the primary transcript is cleaved rapidly behind the ROI, thereby releasing always the same UFM, independent of the ROI sequence, polymerase, or promoter used. The UFM binds to the target of the Spinach aptamer, the fluorogenic dye DFHBI, and thereby induces a strong fluorescence signal. This design allows real-time quantification, standardization, parallelization, and high-throughput screening.
Gesehen am 05.07.2021